2019
DOI: 10.3390/v11040313
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Domain of Spike Protein Is Not the Enteric Tropism Determinant for Transmissible Gastroenteritis Virus in Piglets

Abstract: Transmissible gastroenteritis virus (TGEV) is the etiologic agent of transmissible gastroenteritis in pigs, and the N-terminal domain of TGEV spike protein is generally recognized as both the virulence determinant and enteric tropism determinant. Here, we assembled a full-length infectious cDNA clone of TGEV in a bacterial artificial chromosome. Using a novel approach, the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) systems efficiently and rapidly rescue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Our results confirmed that the enteric tropism determinants are located in the N-terminus of TGEV S protein. Previously published data questioned the relevance of this domain in the enteric tropism [27]. It is worth noting that, in contrast to the data reported by other groups, we compared the tropism of engineered viruses containing a full-length S protein.…”
Section: Receptorsmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results confirmed that the enteric tropism determinants are located in the N-terminus of TGEV S protein. Previously published data questioned the relevance of this domain in the enteric tropism [27]. It is worth noting that, in contrast to the data reported by other groups, we compared the tropism of engineered viruses containing a full-length S protein.…”
Section: Receptorsmentioning
confidence: 92%
“…Then, the contribution of other S protein domains or other viral proteins to enteric tropism was for a long time an open question [26]. In fact, the relevance of S protein N-terminus in TGEV enteric tropism has even recently been questioned [27]. [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although ␣-CoV nsp1 expression is known to suppress host gene expression, its biological functions in viral replication have been largely unexplored. To evaluate the role of TGEV nsp1 in inhibiting host gene expression during viral replication, we used our reverse-genetics system to construct a recombinant TGEV encoding a mutant nsp1 protein in which ORF3 was replaced by green fluorescent protein (GFP) (19). Based on the previously described results, we replaced the important motif (amino acids 91-95) in the nsp1-coding sequence.…”
Section: Construction and Recovery Of A Tgev Mutant Virusmentioning
confidence: 99%
“…with 10% fetal bovine serum. The pBAC-TGEV-GFP plasmid containing a full-length infectious cDNA clone, which was derived from the highly virulent TGEV strain WH-1 (GenBank TM accession number HQ462571), has been described previously (19). To acquire the TGEV recombinant virus, the plasmid was first transfected into HEK-293T cells, and then the virus was recovered to infect virus-susceptible cells.…”
Section: A Conserved Virulence Region Within Alphacoronavirus Nsp1mentioning
confidence: 99%
See 1 more Smart Citation